BIMBINGAN BELAJAR KEPADA PESERTA DIDIK DI SEKOLAH DASAR NEGERI LEGUNDI LAMPUNG SELATAN - Putri, Kadek Yusiana (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2019)
The purpose of this study is (1) Knowing the planning of tutoring based on higher order thinking skills (HOTS) in SD Negeri Legundi, (2) Knowing the implementation of tutoring based on higher order thinking skills (HOTS) in SD Negeri Legundi. HOTS-based learning can hone students' thinking skills to be critical, creative, and able to solve problems. This study uses a qualitative method. The time of this research is from November to January 2021, located at SD Negeri Legundi. The data collected is qualitative data consisting of primary data in the form of semi-structured interviews and non-participatory observations, and secondary data using documentation. The researcher is the main instrument with the tools of interview, observation and documentation. The validity of the data used technical triangulation. The results showed that (1) HOTS-based learning planning was seen in the learning objectives; learning materials; learning Media; tutoring methods; learning evaluation, (2) Implementation of HOTS learning seen from the learning objectives containing cognitive levels C4, C5, and C6; learning material is delivered with problems and is universal; learning media contains material that encourages students' thinking skills; The learning method used is in the form of cooperative learning and there are activities to analyze, evaluate, and create; learning evaluation uses questions that have a stimulus and are open in the realm of analyzing, evaluating or creating.